HUBUNGAN ANTARA KEBIASAAN BURUK BERNAFAS MELALUI MULUT DAN TINGKAT KEPARAHAN MALOKLUSI DI SMPN 4 BANJARBARU DAN SMAN 4 BANJARBARU - Feroza, Nur Avia; Dwi Kurniawan, Fajar Kusuma; Wibowo, Diana (Dentino, 2017)
ABSTRACTBackground: Malocclusion is an oral health problem which occupies in the third place after dental caries and periodontal disease. Data showed that the prevalence of malocclusion in Indonesian teenager was still at a hight rate that reached 90% on 1983 and 89% on 2006. Mouth breathing is a habit that can be the most common causes in the facial structure abnormalities and teeth occlusion. Malocclusion interpreted as occlusion that deviates from normal and cause disruption in the chewing, swallowing, and talking function. Purpose: To determine the correlation between bad habit of mouth breathing to the severity of malocclusion using Handicapping Malocclusion Assessment Record (HMAR). Method: This research uses an observational analytic with cross sectional approach. Samples are adolescents 13-18 years in SMPN 4 Banjarbaru and in SMAN 4 Banjarbaru were selected by random sampling method, 60 people consisting of 30 people in the group who do not breathe through the mouth and 30 people in the group to breathe through the mouth. Results: The results showed that severe malocclusion was more common in the group with mouth breathing was 24 people, while in the group without mouth breathing was 9 people. Statistical analysis with Lambda test obtained significance value of 0.0222 (p-value <0.05). Conclusion: There was a significant relationship between the bad habit of mouth breathing to the severity of malocclusion.Keywords: Handicapping Malocclusion Assessment Record, malocclusion, mouth breathing